Preferred online travel agent: a case of customer reviewed in Thistle Port Dickson Resort / Nur Arina Zainal Abidin dan Nurtisha Shaari - Zainal Abidin, Nur Arina; Shaari, Nurtisha (Faculty of Hotel and Tourism, 2018)
This undergraduate project gives a student knowledge and experience about the research process that very crucial for student to graduate and also for further study. The purpose of this research was to study the element that customer mostly give comment, feedback and review on online travel agent toward Thistle Port Dickson Resort. Based on January 2017 until December 2017 from online travel agent data, the researchers analyses about 548 review that usable. Collected data from the online travel agent review processed by computer program in term of frequency distribution and percentage that used by researchers. The result showed that customer express their experience and feeling in this online travel agent either positive feedback or negative feedback about the value they get. This result can be used by this resort or other hotel to take an improvement for any negative feedback or other hotel can also implement for any positive feedback get from customer to make their customer satisfaction and loyalty.